2015
DOI: 10.1177/2158244015590841
|View full text |Cite
|
Sign up to set email alerts
|

Loss to Follow-Up Among HIV-Exposed Children in an HIV Clinic in Beira, Mozambique

Abstract: Loss to follow-up contributes to the low coverage of HIV care interventions among HIV-exposed infants in Beira, Mozambique. This qualitative study explores the perceptions of HIV-infected women and their health care providers regarding the main obstacles preventing women from attending follow-up visits for HIV care, and factors influencing women's decisions about newborn care. Fifty-two in-depth interviews and two focus group discussions were conducted; transcripts were coded and analyzed using ATLAS.ti. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 20 publications
(46 reference statements)
10
19
0
Order By: Relevance
“…At family and community-level, stigma and fear of discrimination were frequently reported as factors associated with LTFUs, consistent with previous findings 10,12,[14][15][16][17][18]39 .This highlights the need to Household poverty characterized by food shortage was reported as an important factor associated with poor ART adherence and LTFU. This was consistent with previous findings in Malawi 21 and Mozambique 3 . This obviates the need for targeting social safety nets to HIV-affected families as a short-term solution and strengthening of economic empowerment programs as a long-term strategy.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…At family and community-level, stigma and fear of discrimination were frequently reported as factors associated with LTFUs, consistent with previous findings 10,12,[14][15][16][17][18]39 .This highlights the need to Household poverty characterized by food shortage was reported as an important factor associated with poor ART adherence and LTFU. This was consistent with previous findings in Malawi 21 and Mozambique 3 . This obviates the need for targeting social safety nets to HIV-affected families as a short-term solution and strengthening of economic empowerment programs as a long-term strategy.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, both health care workers and the clients reported that clients disengaged from HIV care and sought alternative health care, which is consistent with findings from another study 21 Weaknesses in HIV service delivery characterized by poor staff attitude was cited as an important factor associated with LFTU. This was consistent with findings from previous studies 3,15,17,20,39,54 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The analysis showed no gender effect on loss to follow-up of antiretroviral therapy. This is not in accordance with research by Blanco et al (2015) that women have an effect on the loss to follow-up of antiretroviral therapy, a study by Govindasamy et al (2012) also stated that male sex is at risk of loss to follow-up, a study by Rice et al (2011) stated that women are at risk of loss to follow-up, and a study by Makunde et al (2012) stated that women are at greater risk of loss to follow-up of antiretroviral therapy.…”
Section: Introductionsupporting
confidence: 46%
“…By 2016, the Ministry of Health estimated that 92% of HIV-positive pregnant women were initiated on ART 1 but only 74% of those women were retained in HIV care at 12 months postpartum 2 . Studies done elsewhere have documented similar rates of Loss-To-Follow-Up (LTFU) in HIV care [3][4][5][6][7][8][9] . LFTU breastfeeding mothers, who therefore are not adhering to ART, are at high risk of transmitting HIV to cluster randomized trial compared the effectiveness of three service delivery models for retaining HIV-positive women and their HIV-exposed infants in HIV care.…”
Section: Introductionmentioning
confidence: 99%